Synergetic effect of iron and tungsten on molybdenum‐doped HZSM‐5 zeolite in catalytic methane dehydroaromatization - Ronald. W. Musamali; Yusuf. M. Isa (Energy Science & Engineering)
Abstract Methane dehydroaromatization is a viable route for production of carbon and valuable petrochemicals. Unlike Fischer–Tropsch and methanol synthesis processes which have been scaled up to commercial level, development of methane dehydroaromatization to commercial level has been hampered by various challenges. In this work, a 5.4 wt. % trimetallic (Fe‐W‐Mo/HZSM‐5) catalyst has been synthesized, characterized, and applied in catalytic methane dehydroaromatization reaction. A gas chromatograph was used to analyze both liquid and gaseous products from the reactor. Based on 0.0013 moles of reacted methane after 240 min time on stream at 750 °C, GHSV 960 mlg‐1cath‐1, and atmospheric pressure, a 5.4% Mo/HZSM‐5 catalyst recorded 7.9% methane conversion, 10.6% C2 hydrocarbon selectivity, 51.8% benzene selectivity, 9.8% toluene selectivity and 27.8% coke selectivity. Doping Mo/HZSM‐5 with Fe reduced methane conversion by 4.0%, increased C2 hydrocarbon selectivity by 1.7%, reduced benzene selectivity by 6.2% and increased toluene and coke selectivity by 1.8% and 2.8% respectively. Doping Mo/HZSM‐5 with W increased methane conversion by 7.3%, reduced C2 hydrocarbon selectivity by 2.1%, reduced benzene selectivity by 7.6% and increased toluene and coke selectivity by 0.3% and 9.4% respectively. When iron and tungsten were loaded onto Mo/HZSM‐5, catalytic activity of the tri‐metallic catalyst in methane conversion reduced by 2.0%, C2 hydrocarbon selectivity increased by 2.7%, benzene selectivity reduced by 3.1%, toluene selectivity reduced by 3.7%, and coke selectivity increased by 4.1%. Therefore, this present work demonstrates that metal synergy in a tri‐metallic catalyst plays a role in methane conversion and selectivity towards useful hydrocarbons.